Signs activate their written word translation in deaf adults: An ERP study on cross-modal co-activation in German Sign Language. Issue 1 (12th June 2020) - Hosemann, Jana; Mani, Nivedita; Herrmann, Annika; Steinbach, Markus; Altvater-Mackensen, Nicole
Abstract : Since signs and words are perceived and produced in distinct sensory-motor systems, they do not share a phonological basis. Nevertheless, many deaf bilinguals master a spoken language with input merely based on visual cues like mouth representations of spoken words and orthographic representations of written words. Recent findings further suggest that processing of words involves cross-language cross-modal co-activation of signs in deaf and hearing bilinguals. Extending these findings in the present ERP-study, we recorded the electroencephalogram (EEG) of fifteen congenitally deaf bilinguals of German Sign Language (DGS) (native L1) and German (early L2) as they saw videos of semantically and grammatically acceptable sentences in DGS. Within these DGS-sentences, two signs functioned as prime and target. Prime and target signs either had an overt phonological overlap as signs (phonological priming in DGS), or were phonologically unrelated as signs but had a covert orthographic overlap in their written German translation (orthographic priming in German). Results showed a significant priming effect for both conditions. Target signs that were either phonologically related as signs or had an underlying orthographic overlap in their written German translation engendered a less negative going polarity in the electrophysiological signal compared to overall unrelated control targets. We thus provide first evidence that deaf bilinguals co-activate their secondly acquired 'spoken/written' language German during whole sentence processing of their native sign language DGS.